Lomerizine attenuates LPS-induced acute lung injury by inhibiting the macrophage activation through reducing Ca2+ influx - Song, Yunduan; Gou, Yusen; Gao, Jiameng; Chen, Dongxin; Zhang, Haibo; Zhao, Wenjuan; Qian, Feng; Xu, Ajing; Shen, Yao (Frontiers in Pharmacology, 2023)
Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are life-threatening lung diseases with high mortality rates, predominantly attributable to acute and severe pulmonary inflammation. Lomerizine (LMZ) is a calcium channel blocker previously used in preventing and treating migraine. Here, we found that LMZ inhibited inflammatory responses and lung pathological injury by reducing pulmonary edema, neutrophil infiltration and pro-inflammatory cytokine production in lipopolysaccharide (LPS)-induced ALI mice. In in vitro experiments, upon treating with LMZ, the expression of interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α was attenuated in macrophages. The phosphorylation of p38 MAPK, ERK1/2, JNK, and NF-κB p65 was inhibited after LMZ treatment. Furthermore, LPS-induced Ca 2+ influx was reduced by treating with LMZ, which correlated with inhibition of proinflammatory cytokine production. And L-type Ca 2+ channel agonist Bay K8644 (BK) could restore cytokine generation. In conclusion, our study demonstrated that LMZ alleviates LPS-induced ALI and is a potential agent for treating ALI/ARDS.